Hard low-friction TaCN / NbCN nano multilayer film and preparation method thereof

The preparation of TaCN/NbCN nano-multilayer films through multi-target magnetron sputtering technology has solved the brittleness of existing high wear-resistant materials under high speed, high temperature and high load conditions, and achieved high hardness, low friction coefficient and excellent material wear resistance.

CN119491197APending Publication Date: 2025-02-21JINAN CHUANGKE ELECTRONIC TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411686125.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing high-wear resistant materials are prone to fracture under high speed, high temperature and high load conditions, and their performance is limited in high temperature environments, which cannot meet the needs of modern industry for high-performance materials.

Method used

Multi-target magnetron sputtering technology is used to prepare TaCN/NbCN nanolayers with alternate stacked TaCN and NbCN nanolayers, and superhard phenomena are achieved by optimizing the deposition parameters.

Benefits of technology

It realizes the high hardness, low friction coefficient and excellent wear resistance of the material, significantly improves the hardness of the material and reduces the friction coefficient, and is suitable for high-speed, high temperature and high load working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119491197A_ABST
    Figure CN119491197A_ABST
Patent Text Reader

Abstract

The invention relates to a hard low-friction TaCN / NbCN nano multilayer film and a preparation method thereof. The nano multilayer film belongs to the technical field of coating preparation. The nano multilayer film is composed of TaCN layers and NbCN layers which are alternately stacked, and nitrogen is doped in TaC and NbC, so that the hardness of the film is improved, and the friction coefficient is reduced. The thickness of the modulation layer has a significant influence on hardness, and the multilayer film has a good periodic structure. The TaCN / NbCN nano-multilayer film provided by the invention is used as a protective coating, so that the friction coefficient of a material can be remarkably reduced, and the wear resistance and hardness of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a hard low-friction TaCN / NbCN nano multilayer film and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, especially in high-end technology fields such as aerospace, automobile manufacturing and microelectronics, the performance requirements of materials are increasing. The wear resistance of materials has become a key factor in determining their performance and life in engineering applications, especially under high-speed, high-temperature and high-load working conditions. Therefore, the development of new materials with excellent wear resistance has become a research hotspot in the field of materials science. Traditional high-wear-resistant materials, such as cemented carbide and ceramic materials, have high hardness and wear resistance, but due to their high brittleness and poor toughness, they are prone to fracture under impact loads, which limits their scope of application. At the same time, the performance of these materials in high temperature environments is also limited, and they cannot meet the needs of modern industry for high-performance materials. Therefore, finding a new material with high hardness, high toughness and low friction coefficient has become an urgent problem to be solved.

[0003] Transition metal carbide films are widely used as surface protective coatings in aerospace, automotive industry, mechanical processing, geological drilling and other fields due to their excellent physical and chemical properties such as high hardness, high melting point, low friction coefficient, wear resistance, corrosion resistance and oxidation resistance. TaC and NbC, as representatives of this type of materials, have attracted much attention due to their excellent performance. However, single-layer films have disadvantages in structural complexity, characteristics and functions, performance and reliability, residual stress and thermomechanical integrity, which limit the use of single-layer films in high-performance applications. Multilayer films show greater advantages in many advanced applications due to their diversity and customizability in structure and performance. Multi-arc ion plating technology is one of the commonly used coating methods for the preparation of nano-multilayer films. However, the method of frequently opening and stopping the multi-arc target alternately is generally used to prepare nano-multilayer films using this technology, which results in a large number of large droplets ejected each time the target is opened, resulting in an increase in large particles in the film, which seriously affects the quality of the film. In order to solve the shortcomings of the existing technology, this paper adopts multi-target magnetron sputtering technology to provide a TaCN / NbCN nano-multilayer film material with high hardness, low friction coefficient and high wear resistance and a preparation method thereof. By optimizing the deposition parameters, this film can deposit TaCN / NbCN nano-multilayer films on cemented carbide or ceramic substrates to achieve superhardness.

[0004] The present invention is proposed in this context, and aims to provide a hard, low-friction TaCN / NbCN nano-multilayer film and a preparation method thereof, so as to solve the above-mentioned problems in the prior art and meet the demand of modern industry for high-performance materials. Summary of the invention

[0005] The purpose of the present invention is to provide a hard low-friction TaCN / NbCN nano multilayer film and a preparation method thereof. The low-friction TaCN / NbCN nano multilayer film provided by the present invention is used as a protective coating for metals, which can significantly improve the hardness of the material and reduce the friction coefficient.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A hard low-friction TaCN / NbCN nano multilayer film comprises TaCN nanolayers and NbCN nanolayers which are alternately stacked, wherein the bottom layer is a TaCN layer and the surface layer is a NbCN layer, and both the TaCN layer and the NbCN layer are nanocrystalline.

[0007] The thickness ratio of the TaCN layer and the NbCN layer formed in one modulation cycle is about 1:1, and the total thickness of the TaCN / NbCN nanomultilayer film is between 600 and 700 nm.

[0008] Preferably, the thickness of the TaCN nanolayer or the NbCN nanolayer is 4-30 nm.

[0009] Preferably, the compositions of the TaCN layer and the NbCN layer are: 51 at.% Ta, 29 at.% C, 20 at.% N, 57 at.% Nb, 24 at.% C, 19 at.% N, respectively.

[0010] The present invention provides a method for preparing the friction-resistant TaCN / NbCN nano multilayer film described in the above technical solution, comprising the following steps: The multi-target magnetron sputtering technology was adopted to alternately sputter the substrate with TaC target and NbC target as the sputtering target materials to obtain the friction-resistant TaCN / NbCN nano-multilayer film.

[0011] Preferably, the atomic percentage ratios of Ta and C as well as Nb and C in the TaC target and the NbC target are both 1-2.

[0012] Preferably, the step of alternate sputtering is: under vacuum conditions, open the baffles of the TaC target and the NbC target, and 2 The sputtering was carried out alternately in an Ar atmosphere, wherein the gas flow rate was 60-80 sccm, N 2 The gas flow rate is 15~20 sccm, the gas pressure of alternating sputtering is 0.6~1.0 Pa, the bias voltage of the substrate is -60~-200 V, the sputtering current of the TaC target is 0.1~0.5 A, the sputtering current of the NbC target is 0.1~0.5 A, and the substrate rotation speed is 1~10 r / min.

[0013] Preferably, during the alternating sputtering, the vacuum condition is not higher than 5×10 -4Pa, the distance between the TaC target, the NbC target and the substrate is 60-80 mm, the sputtering current of both the TaC target and the NbC target is controlled by a DC power supply and the sputtering current is 0.1-0.5 A, the sputtering time of the TaCN layer is 8-60 s, and the sputtering time of the NbCN layer is 10-74 s. One TaCN layer and one NbCN layer are taken as a modulation cycle. After repeated alternating deposition to the preset modulation cycle, the TaCN / NbCN nano-multilayer film is obtained by cooling to room temperature.

[0014] Preferably, the substrate is at least one of a silicon wafer, a Ti-6Al-4V wafer, and a stainless steel wafer.

[0015] The present invention provides the use of the friction-resistant TaCN / NbCN nano-multilayer film described in the above technical solution or the friction-resistant TaCN / NbCN nano-multilayer film prepared by the preparation method described in the above technical solution as a protective coating.

[0016] The present invention provides a hard, low-friction TaCN / NbCN nano-multilayer film, comprising TaCN nano-layers and NbCN nano-layers alternately stacked; the TaCN / NbCN nano-multilayer film has a good periodic structure. In the present invention, the TaCN / NbCN nano-multilayer film has a high hardness and can provide mechanical support; and during the friction process, both the TaCN nano-layer and the NbCN nano-layer can produce lubricating substances. The TaCN / NbCN nano-multilayer film constructed by the present invention can combine the advantages of each nano-layer and integrate high hardness and excellent tribological properties through the synergistic effect of each nano-layer to obtain a friction-resistant nano-multilayer film. The friction-resistant TaCN / NbCN nano-multilayer film provided by the present invention has both high hardness and excellent tribological properties, and can be used as a friction-resistant protective coating to solve the problem that the surface of the material is prone to wear. Using the friction-resistant TaCN / NbCN nano-multilayer film provided by the present invention as a protective coating for the material can significantly improve the hardness of the material and reduce the friction coefficient of the material.

[0017] The friction-resistant TaCN / NbCN nano multilayer film provided by the present invention has the following beneficial effects: (1) The present invention uses two thin film materials, TaCN and NbCN, with high hardness and high wear resistance, to prepare nano-multilayer films, and proposes a more suitable modulation period range for the two materials: TaCN is 4~30 nm, and NbCN is 4~30 nm. The two thin film materials are deposited alternately to reduce the interface shear stress and improve the wear resistance.

[0018] (2) The TaCN / NbCN nano-multilayer film prepared under the above-mentioned modulation period conditions of the present invention combines the advantages of the two thin film materials, and has a hardness of up to 42.88 GPa, which is a superhard film. The friction coefficient is as low as 0.19, and the friction and wear performance is excellent.

[0019] (3) TaCN and NbCN are typical representatives of multi-component superhard films. The proper addition of N elements can improve the performance of binary TaC and NbC films. In TaCN and NbCN, N atoms partially replace C atoms in Ta-C and Nb-C bonds to generate Ta-N and Nb-N bonds, and cause lattice distortion in TaCN and NbCN, which significantly improves their hardness. After friction, the C element in TaCN and NbCN mainly exists in the form of amorphous carbon, which plays a very important lubricating role in the friction process. In addition, self-lubricating oxides (NbO x 、TaO x ), so the TaCN / NbCN nano-multilayer film has excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the preparation of TaCN / NbCN nano multilayer film according to the present invention.

[0021] Figure 2 This is the XRD diagram of the TaCN / NbCN nano-multilayer film prepared in the present invention.

[0022] Figure 3 This is a TEM cross-sectional view of the TaCN / NbCN nano-multilayer film prepared in the present invention.

[0023] Figure 4 The hardness and elastic modulus of the films prepared in the embodiments of the present invention and the comparative examples are shown.

[0024] Figure 5 The friction coefficient curve and wear rate line graph of the samples prepared in the implementation examples and comparative examples of the present invention. DETAILED DESCRIPTION

[0025] The invention provides a hard low-friction TaCN / NbCN nano-multilayer film, comprising a transition layer TaC and alternately stacked TaCN nano-layers and NbCN nano-layers; the TaCN / NbCN nano-multilayer film has good periodicity.

[0026] In the present invention, a TaCN nanolayer and a NbCN nanolayer stacked in sequence are taken as one modulation period, and the number of modulation periods of the friction-resistant TaCN / NbCN nanomultilayer film is preferably 10 to 75; the thickness ratio of the TaCN nanolayer and the NbCN nanolayer in each modulation unit is preferably 1:1.

[0027] In the present invention, the thickness of each TaCN nanolayer or NbCN nanolayer is preferably 4-30 nm.

[0028] The present invention provides a method for preparing the friction-resistant TaCN / NbCN nano multilayer film described in the above technical solution, comprising the following steps: The multi-target magnetron sputtering technology was adopted, with TaC target as the pre-sputtering target, and then TaC target and NbC target as the alternating sputtering targets to sputter the substrate alternately, thereby obtaining the friction-resistant TaCN / NbCN nano-multilayer film.

[0029] In the present invention, the substrate is preferably a silicon wafer. In the present invention, the substrate is preferably pretreated before use. In the present invention, the pretreatment preferably includes cleaning and drying performed in sequence. In the present invention, the cleaning preferably includes: using acetone and alcohol and deionized water in an ultrasonic cleaning machine for 20 minutes respectively. In the present invention, the drying preferably includes: drying in a drying oven. A cleaned and dried substrate is obtained.

[0030] In the present invention, the sputtering gas used in the magnetron sputtering is preferably argon and nitrogen. In the present invention, the purity of the argon and nitrogen is preferably 99.995-99.999%, the gas flow rate of Ar is 60-80 sccm, and the gas flow rate of N is 1. 2 The gas flow rate is 15~20 sccm.

[0031] In the present invention, before the alternating sputtering is performed, the vacuum degree in the coating chamber of the magnetron sputtering system is preferably better than 8×10 -4 Pa. The present invention maintains the vacuum degree in the coating chamber of the magnetron sputtering system within the above range, and can discharge gas impurities in the coating chamber to the maximum extent, thereby avoiding contamination of samples during the coating process.

[0032] In the present invention, the substrate is preferably kept rotating during the alternating sputtering process. In the present invention, the substrate is rotated at a speed of 1 to 10 r / min. The present invention keeps the substrate rotating within the above range, so that the formed thin film can be uniform. The working gas pressure of the alternating sputtering process is preferably 0.6 to 1.0 Pa. The present invention uses the above working gas pressure to ensure that the deposition rate is optimal.

[0033] In the present invention, the diameter of the TaC target and the NbC target is preferably 60 mm, and the purity is preferably 99.999%.

[0034] In the present invention, the TaC target and the NbC target preferably use a DC power supply; the sputtering current of the TaC target and the NbC target is preferably 0.1-0.5 A; and the distance between the TaC target, the NbC target and the substrate is preferably 60-80 mm.

[0035] In a specific embodiment of the present invention, sputtering gases Ar and N are introduced during the deposition of the friction-resistant TaCN / NbCN nano-multilayer film. 2, adjust the working pressure in the coating chamber, set the current of the sputtering power supply, and control the rotation of the substrate so that the substrate surface faces the TaC target and the NbC target alternately. A modulation cycle of sequentially depositing TaCN nanolayers and NbCN nanolayers is obtained on the substrate surface, and a continuous nano-multilayer film structure is formed through the accumulation of modulation cycles.

[0036] In the present invention, it is preferred that after the alternating sputtering is completed, the vacuum is continued to be maintained at 5×10 -4 Pa and the multilayer film was cooled to room temperature to obtain a TaCN / NbCN nano-multilayer film.

[0037] In a specific embodiment of the present invention, the method for preparing the friction-resistant TaCN / NbCN nano multilayer film is as follows: Figure 1 As shown, a TaC transition layer is first deposited for 3 min, and then TaCN / NbCN nano-multilayers are alternately deposited, with the TaCN or NbCN layer being 4 to 30 nm.

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0039] Example 1 The preparation method of the coating is: 1) Clean and dry the substrate; specifically, place the substrate in an acetone solution for ultrasonic cleaning for 20 min; then place the substrate in alcohol for ultrasonic cleaning for 20 min; finally, ultrasonic clean the substrate in deionized water for 20 min, take it out and place it in a drying oven at 50~80 ˚C for 0.5~1h; 2) Using magnetron sputtering equipment, the cleaned and dried substrate was placed in the vacuum chamber of the magnetron sputtering device. The distance between the TaC target and the NbC target and the substrate was 80 mm. The bias voltage of the substrate was adjusted to -80 V, and the chamber was evacuated to 5×10 -4 Below Pa; 3) Close the baffle of the NbC target, open the baffle of the TaC target, and introduce sputtering gas Ar for pre-sputtering; wherein, the gas flow rate of Ar is set to 60 sccm; the working pressure of the vacuum chamber is adjusted to 0.8 Pa; the sputtering current of the TaC target is 0.3 A, and the sputtering time is 3 min; 4) After the pre-sputtering is completed, the sputtering parameters are adjusted to the predetermined parameters, the baffles of the TaC target and the NbC target are opened, and the sputtering gases Ar and N are introduced. 2 , alternately sputtering to deposit TaCN / NbCN nano multilayer film on the substrate surface; wherein, N 2The gas flow rates of TaC and NbC were 15 / 60 sccm respectively; the working pressure of the vacuum chamber was adjusted to 0.8 Pa; the sputtering current of the TaC target was 0.3 A, and the sputtering current of the NbC target was 0.3 A. In one modulation cycle, the deposition time of TaCN was 8 s, and the deposition time of NbCN was 10 s. A total of 75 cycles were deposited, and the substrate rotation speed was 10 r / min during the deposition process.

[0040] 5) After the sputtering of the nano-multilayer film is completed, the chamber is further evacuated, and the TaCN / NbCN nano-multilayer film sample obtained in step 4) is cooled to room temperature along with the chamber, and then the vacuum system is closed to obtain the TaCN / NbCN nano-multilayer film, thereby completing the friction-resistant nano-multilayer film.

[0041] The thickness of the obtained TaCN / NbCN nano multilayer film is about 620 nm. The hardness of the TaCN / NbCN nano multilayer film obtained in this example is as follows: Figure 4 The film hardness is 36.39 GPa. The friction test of the TaCN / NbCN nano multilayer film obtained in this embodiment is carried out. The friction coefficient curve and wear rate are shown in Figure 5 The friction coefficient is 0.22 and the wear rate is 13.17×10 −7 mm 3 / Nm.

[0042] Example 2 The difference from Example 1 is that in step 4), the deposition time of TaCN is 30 s, the deposition time of NbCN is 37 s, and the total deposition is 20 cycles.

[0043] The rest is the same as in Example 1 and will not be described again here.

[0044] The thickness of the obtained TaCN / NbCN nano multilayer film is about 650 μm. The hardness of the TaCN / NbCN nano multilayer film obtained in this example is as follows: Figure 4 The film hardness is 42.88 GPa. The friction test of the TaCN / NbCN nano multilayer film obtained in this embodiment is carried out. The friction coefficient curve and wear rate are shown in Figure 5 The friction coefficient is 0.19 and the wear rate is 0.86×10 −7 mm 3 / Nm.

[0045] Example 3 The difference from Example 1 is that in step 4), the deposition time of TaCN is 60 s, the deposition time of NbCN is 74 s, and the deposition is performed for 10 cycles.

[0046] The rest is the same as in Example 1 and will not be described again here.

[0047] The thickness of the obtained TaCN / NbCN nano multilayer film is about 700 nm. The hardness of the TaCN / NbCN nano multilayer film obtained in this example is as follows: Figure 4 The film hardness is 34.74 GPa. The friction test of the TaCN / NbCN nano multilayer film obtained in this embodiment is carried out. The friction coefficient curve and wear rate are shown in Figure 5 The friction coefficient is 0.23 and the wear rate is 1.49×10 −7 mm 3 / Nm.

[0048] It can be seen from Examples 1 to 3 that the performance of the TaCN / NbCN nano-multilayer film is determined by the modulation period. As the modulation period gradually increases, the hardness and wear resistance first increase and then decrease. The best performance is achieved when the modulation period is 15:15 nm. That is, the most suitable modulation period and modulation ratio conditions for the TaCN / NbCN nano-multilayer film of the present invention are: TaCN is 15 nm and NbCN is 15 nm.

[0049] Comparative Example 1 1) Clean and dry the substrate; specifically, place the substrate in an acetone solution for ultrasonic cleaning for 20 min; then place the substrate in alcohol for ultrasonic cleaning for 20 min; finally, ultrasonic clean the substrate in deionized water for 20 min, take it out and place it in a drying oven at 50~80 ˚C for 0.5~1h; 2) Using magnetron sputtering equipment, the cleaned and dried substrate was placed in the vacuum chamber of the magnetron sputtering device. The distance between the TaC target and the substrate was 80 mm. The bias voltage of the substrate was adjusted to -80 V, and the chamber was evacuated to 5×10 -4 Below Pa; 3) Adjust the sputtering parameters to the set parameters, open the baffle of the TaC target, and introduce sputtering gases Ar and N 2 , sputtering is performed to deposit a TaCN film on the surface of the substrate; wherein, N 2 The gas flow rates of / Ar were 15 / 60 sccm respectively; the working pressure of the vacuum chamber was adjusted to 0.8 Pa; the sputtering current of the TaC target was 0.3 A, and the sputtering time was 30 min; 4) After the sputtering is completed, the chamber is further evacuated, and the TaCN single-layer film sample obtained in step 3) is cooled to room temperature along with the chamber, and then the vacuum system is closed to obtain the TaCN single-layer film, thereby completing the friction-resistant nano multilayer film.

[0050] The hardness of the obtained TaCN film is as follows Figure 4 The hardness is 36.4 GPa. The friction test of the TaCN film obtained in this embodiment is carried out. The friction coefficient curve and wear rate are shown in Figure 5The friction coefficient is 0.2 and the wear rate is 7.13871×10 −7 mm 3 / Nm.

[0051] Comparative Example 2 The difference from Comparative Example 1 is that in step 3), the baffle of the NbC target is opened, the sputtering current of the NbC target is 0.3 A, and the sputtering time is 30 min.

[0052] The rest is the same as Comparative Example 1 and will not be described again.

[0053] The hardness of the obtained NbCN film is as follows Figure 4 The hardness is 26.15 GPa. The friction test of the NbCN film obtained in this embodiment is carried out. The friction coefficient curve and wear rate are shown in Figure 5 The friction coefficient is 0.25 and the wear rate is 8.0807×10 − 7 mm 3 / Nm.

[0054] See also Figure 2-5 The TaCN / NbCN nano-multilayer film has nanocrystalline components, TaCN layer and NbCN layer, and the layer thickness is stable in the nanometer size range. The hardness of the nano-multilayer film is higher than that of the single-layer film. When the modulation period is 15:15nm, the optimal hardness is 42.88 GPa, the friction coefficient is 0.19, and the wear rate is 0.86×10 −7 mm 3 / Nm; therefore, the TaCN / NbCN nano multilayer film provided by the present invention has high hardness and excellent wear resistance.

[0055] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and scope of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A hard low-friction TaCN / NbCN nano-multilayer film, characterized in that: It comprises TaCN layers and NbCN layers which are alternately arranged, wherein the bottom layer is the TaCN layer and the surface layer is the NbCN layer, and both the TaCN layer and the NbCN layer are nanocrystalline.

2. The TaCN / NbCN nano-multilayer film according to claim 1, characterized in that: A modulation period is formed by alternating a layer of TaCN and a layer of NbCN. The thickness ratio of the TaCN layer and the NbCN layer formed in one modulation period is about 1:

1. The compositions of the TaCN layer and the NbCN layer are: 51 at.% Ta, 29 at.% C, 20 at.% N, 57 at.% Nb, 24 at.% C, 19 at.% N, respectively. The total thickness of the TaCN / NbCN nano-multilayer film is 700-900 nm, and its hardness is 34-42 GPa.

3. The friction-resistant TaCN / NbCN nano-multilayer film according to claim 1 or 2, characterized in that: The single layer thickness of TaCN or NbCN is 4-30 nm, and the total number of modulation periods is 10-75.

4. The method for preparing the friction-resistant TaCN / NbCN nano multilayer film according to any one of claims 1 to 3, characterized in that: The method comprises adopting multi-target magnetron sputtering technology, using TaC target and NbC target as sputtering target materials to sputter the substrate alternately, so as to obtain a friction-resistant TaCN / NbCN nano multilayer film.

5. The preparation method according to claim 4, characterized in that: The atomic percentage ratios of Ta and C as well as Nb and C in the TaC target and the NbC target are both 1-2.

6. The method for preparing the friction-resistant TaCN / NbCN nano multilayer film according to claim 4, characterized in that: Before alternating sputtering, the substrate is pre-sputtered. The pre-sputtering steps are as follows: open the TaC target baffle and pre-sputter the substrate in an Ar gas atmosphere, wherein the Ar gas flow rate is 60-80 sccm, the pre-sputtering gas pressure is 0.6-1.0 Pa, the pre-sputtering current of the TaC target is 0.1-0.5 A, the pre-sputtering time is 3-5 min, and the substrate rotation speed is 1-10 r / min.

7. The preparation method according to claim 4, characterized in that: The spacing between the TaC target, the NbC target and the substrate is 60-80 mm. The alternating sputtering step is as follows: under vacuum conditions, the baffles of the TaC target and the NbC target are opened, and sputtering is performed alternately in an Ar gas and N2 gas atmosphere, wherein the Ar gas flow rate is 60-80 sccm, the N2 gas flow rate is 15-20 sccm, the gas pressure of the alternating sputtering is 0.6-1.0 Pa, and the substrate bias voltage is -60--100 V.

8. The preparation method according to claim 7, characterized in that: Both TaC and NbC targets were sputtered with a DC power supply to control the sputtering current, and the sputtering current was 0.1-0.5 A. The vacuum condition before sputtering was no higher than 5×10 -4 Pa, the sputtering time of TaCN layer is 8~60 s, the sputtering time of NbCN layer is 10~74 s, one TaCN layer and one NbCN layer is regarded as a modulation cycle, after repeated alternating deposition to the preset modulation cycle, the TaCN / NbCN nano-multilayer film is obtained after cooling to room temperature.

9. Use of the friction-resistant TaCN / NbCN nano-multilayer film according to any one of claims 1 to 3 or the friction-resistant TaCN / NbCN nano-multilayer film prepared by the preparation method according to any one of claims 4 to 8 as a protective coating.